A program for approximating the control ARL for the MEWMA chart. - Bodden, Kevin M.
The multivariate exponentially weighted moving average (MEWMA) control chart is a control charting scheme that uses weighted averages of previously observed random vectors to monitor the mean vector of a process. The in control average run length (ARL) for the MEWMA control chart can be expressed as the solution of an integral equation. We give a FORTRAN program that uses the quadrature method to approximate the solution of this integral equation. The program can be used to obtain either the in-control ARL for a given value of the upper control limit or the appropriate upper control limit for a desired in control ARL.